ANALISIS PENGARUH DEBT TO EQUITY RATIO, RETURN ON EQUITY, CURRENT RATIO, OPERATING PROFIT MARGIN DAN INFLASI TERHADAP HARGA SAHAM (Studi Pada Perusahaan Barang Konsumsi Yang Terdaftar di BEI ) - Murdam; JMV, Mulyadi; Wiratno, Adi (EKOBISMAN : JURNAL EKONOMI BISNIS MANAJEMEN, 2018)
This study aims to analyze and examine the effect of Debt to Equity Ratio (DER), Return on Equity (ROE), Current Ratio (CR), Operating Profit Margin (NPM) and Inflation on stock prices. This research was taken because there are still differences in research between one research to another and there is a difference between the real state of research data with the existing theory. This research was conducted using secondary data. The sample used in this study is a consumer goods company listed on the Indonesia Stock Exchange for the 2012-2017 period. The sample technique used is purposive sampling. The analysis method used is multiple linear regression analysis. The results showed that Debt to Equity Ratio (DER) partially had a positive and insignificant effect on stock prices. Return on Equity (ROE) partially has a positive and insignificant effect on stock prices. Current Ratio (CR) partially has a negative and significant effect on stock prices. Operating Profit Margin (OPM) partially has a positive and significant effect on stock prices while inflation partially has a negative and insignificant effect on stock prices.